2011
DOI: 10.1186/1471-2156-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Detection of QTL with effects on osmoregulation capacities in the rainbow trout (Oncorhynchus mykiss)

Abstract: BackgroundThere is increasing evidence that the ability to adapt to seawater in teleost fish is modulated by genetic factors. Most studies have involved the comparison of species or strains and little is known about the genetic architecture of the trait. To address this question, we searched for QTL affecting osmoregulation capacities after transfer to saline water in a nonmigratory captive-bred population of rainbow trout.ResultsA QTL design (5 full-sib families, about 200 F2 progeny each) was produced from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 61 publications
(74 reference statements)
3
55
1
Order By: Relevance
“…Our results provide data from natural populations in California and Oregon that support prior studies on diverse O. mykiss lineages using candidate genes, genome wide association and QTL mapping to explore the genetic architecture of traits associated with life history in O. mykiss, including migration [17,32,42,46,48,[65][66][67][68][69][70][71][72][73][74][75][76]. Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70].…”
Section: Discussionsupporting
confidence: 74%
“…Our results provide data from natural populations in California and Oregon that support prior studies on diverse O. mykiss lineages using candidate genes, genome wide association and QTL mapping to explore the genetic architecture of traits associated with life history in O. mykiss, including migration [17,32,42,46,48,[65][66][67][68][69][70][71][72][73][74][75][76]. Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70].…”
Section: Discussionsupporting
confidence: 74%
“…Washington and Idaho; Le Bras et al 2011 Genomic regions linked to embryonic development and breeding timing under differential selection between resident and anadromous individuals.…”
Section: Anadromymentioning
confidence: 99%
“…This is likely due to the wide diversity and suitability of fishes for transfer experiments, as movement between high and low salinities is an essential part of the ontogeny and reproductive cycle of many species (43). Quantitative trait locus (QTL) studies on Arctic charr (Salvelinus alpinus) (47), Atlantic salmon (Salmo salar) (48), and rainbow trout (Oncorhynchus mykiss) (31) show that intraspecific variation in osmoregulatory capacity amid hyperosmotic conditions (i.e., hypo-osmoregulation) is shaped, in part, by allelic variation. However, QTL experiments involving nonmodel organisms such as these typically suffer from drawbacks that can impair QTL detection.…”
mentioning
confidence: 99%